Paying the Cradle's Bill: The Long Term Economic Consequences of Economic Crises - Carlos Bozzoli (Weekly Report, 2010)
Argentina hit world news headlines in 2002 due to the largest debt-default in history and a sudden economic collapse reminiscent of economic statistics from the Great Depression. In this article, we focus on other consequences of the crisis that are not so obvious, but that may linger for decades on. Using the case of Argentina, we examine the long-term consequences of adverse economic conditions for those born during the crisis. We focus on birth weight - a key indicator of health at birth - and the effects that this has on the income of the cohort born during the crisis, to illustrate how a "cradle bill" may emerge in these situations. We find that in just about 6 months, the birth weight of newborns in a middle-high income country like Argentina deteriorated in a magnitude that is comparable to 1/6th the difference in birth weight between American and Pakistani babies. These results are also stunning because such disruption in health status occurred in a country with a similar ratio of physicians per person than Germany or Norway. We estimate the average loss of future individual earnings due to the reduction in average birth weight is about 500 US-Dollars in present value. This is a conservative estimate because it does not include other potential losses not reflected in lifetime earnings, for example life-time health care costs or a reduction in life expectancy. This "bill" will not be paid equally, since poor mothers are most affected in terms of birth weight, which may exacerbate income inequalities in the long run. The policy implications of these findings are not solely relevant for developing countries, but also for developed countries in terms of setting priorities in aid strategies to countries under economic distress.
Keywords: I12; J13; 330; birthweight; economic crises; health production; long term impact